Analisis Prestasi Pompa Air Pada Mesin Bottled Line Automatic Controller (Blac) - Joel Padde Tamba; Deri Teguh Santoso; Viktor Naubnome (Jurnal Ilmiah Wahana Pendidikan, 2022)
Water is the source of life, because no living thing can survive without water. We are always trying to get water. One of the most common tools in water treatment is a water pump. In its application, the use of this water pump is used in the Bottled Line Automatic Controller (BLAC) automatic gallon filling machine. As for the place of assembly and this research was carried out at PT. Desalite Tirtamas Technology, Bintaro, Tangerang Selatan. For this Reason, information is needed regarding the perfomance of the water pump on the BLAC engine, to find out the variables that can be improved in order to increase the performance of the BLAC engine itself. The result showed that the increase in the hydraulic power of the pump continuously resulted in an increase in discharge which was influenced by how big the valve was, where the bigger the torque. The highest discharge value at 100% valve opening is 0,00111 and 0,0004773 at 50% valve opening, where the shaft power value at 100% valve opening is 1165,56 watts, and the 50% valve opening is 1049,004 watts. With the most efficient performance at the largest valve opening, 100% valve opening with a value of 31,73 and 19,038 at 50% valve opening.